RELATIONSHIP PREECLAMPSIA WITH PREMATURE LABOR IN JOMBANG REGIONAL GENERAL HOPITAL ON JUNE IN THE YEAR 2019 th - Ika Nuriza, Ananda; Na'im, Semi; Hidayah, Ardiyanti (LPPM STIKES HUSADA JOMBANG, 2020)
Preeclampsia is pregnancy disorder that characterized clinical symptoms of hypertension, urine protein, edema, at gestational age >20weeks-48hours after delivery. Premature labor is labor that occurs at gestational age >20weeks <37weeks, or with fetal weight <2500gram. This study to determine relationship preeclampsia with premature labor in Jombang Regional General Hospital. Study design used is non-experimental observations with correlational design or analytical survey approach retrospectively. Population all maternal preeclampsia 80respondents. Samples included 80respondents. Sampling using total sampling technique, independent variable preeclampsia and dependent variable preterm labor, to determine relationship between variables used Chi-Quadrat correlation test. Results of more than half respondents had preeclampsia 50respondents (62.5%), almost half respondents severe preeclampsia 30respondents (37.5%). Most respondents didn’t experience preterm birth 55respondents (68.8%), almost half preterm labor as much as 25respondents (31.2%). The results Chi-Quadrat analysis get p value = 0.001 < α = 0.05, H1 accepted, There’s relationship between preeclampsia with preterm labor in Jombang General Hospital. Chi-Quadrat correlation value 0.346 according interpretation table included in range 0.200-0.399 that weak interpretation. Attempts overcome these problems counseling about preeclampsia in pregnant women be mothers know about preeclampsia. Signs, symptoms, impact so that women are more cautious and careful in maintaining health.